Graphic memory of printed color: microscopy, data visualization, and AI-assisted analysis of nineteenth-century chromolithographic materials - Barros, Helena de (InfoDesign, 2026)
This article presents a synthesis of the methodological procedures that have grounded the author’s research on printed color and graphic language, with a focus on the interface between visual memory and information design. The framework, developed and consolidated in previous publications, has proved effective for the analysis of nineteenth-century graphic materials. The present formulation emerges from an invited lecture at CIDI 2025 and highlights processes of microscopy, color sampling, taxonomic organization, and data visualization, focusing on the formal strategies that support the examination of complex chromatic layering. The method was applied to Brazilian institutional collections and, more recently, to the Twyman Collection (University of Reading), allowing for structural comparisons between distinct chromatic sets.